2022
DOI: 10.3390/molecules27154916
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Effects on the Reproductive System in Ovariectomized Rats: Deciphering Possible Mechanisms

Abstract: Phytoestrogen resveratrol (R) has been demonstrated to benefit human reproductive health. However, R bioavailability and pharmacokinetics are still problematic under oral supplementation. We used an experimental vaginal gel with R and hyaluronic acid (HA) to improve bioavailability and pharmacokinetic properties. The study aimed to assess the impact of vaginal R-HA gel on the reproductive system in ovariectomized rats. Methods: The study was carried out on Wistar female rats. It investigated the body weight, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…28,29 Under extreme conditions, the total number of neurons in the hippocampus declines. 30,31 The recorded asymmetry of hippocampal morphological changes is consistent with the available literature data on the existence of interhemispheric asymmetry of hippocampal cytoarchitectonics both in the normal state and in the conditions of adaptive response of brain components. [32][33][34][35] The studies of the rat thyroid gland allowed identifying some features of its microstructural organization, establishing morphological criteria for functional activity, and determining the role of the gland in adaptive processes under conditions of heat stress.…”
Section: Discussionsupporting
confidence: 89%
“…28,29 Under extreme conditions, the total number of neurons in the hippocampus declines. 30,31 The recorded asymmetry of hippocampal morphological changes is consistent with the available literature data on the existence of interhemispheric asymmetry of hippocampal cytoarchitectonics both in the normal state and in the conditions of adaptive response of brain components. [32][33][34][35] The studies of the rat thyroid gland allowed identifying some features of its microstructural organization, establishing morphological criteria for functional activity, and determining the role of the gland in adaptive processes under conditions of heat stress.…”
Section: Discussionsupporting
confidence: 89%
“…It has been observed that resveratrol (RES) reduces inflammation and possesses, antioxidant, antiproliferative, proapoptotic, anticancer, neuroprotective, antiviral, and antiaging actions [13]. It has direct ROS scavenging activities and can enhance endogenous antioxidant cellular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Women with longer maternity leave and access to lactation support in the workplace are more likely to continue exclusive breastfeeding for the recommended six months. In addition, public health interventions that address social and economic inequalities have played a key role in promoting breastfeeding practices at the community level [30][31][32]. Such initiatives have been aimed at improving breastfeeding support and awareness among underserved populations, reducing the breastfeeding gap between different socioeconomic groups.…”
Section: Discussionmentioning
confidence: 99%